2020
DOI: 10.1007/s00401-020-02183-1
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor 2 (IGF2) protects against Huntington’s disease through the extracellular disposal of protein aggregates

Abstract: Insulin-like growth factor 2 (IGF2) protects against Huntington´s disease through the extracellular disposal of protein aggregates.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 114 publications
(121 reference statements)
2
49
0
Order By: Relevance
“…Instead, IGF2 treatment enhanced the nonconventional disposal of soluble polyglutamine peptide species into the extracellular space through the secretion via microvesicles and exosomes. Knockdown of IGF2R decreased almost in half the levels of polyQ79-EGFP secretion, whereas the knockdown of IR or IGF1R did not have any effect on this [49]. Similar results were obtained in a study using a genetic model of AD: in the primary hippocampal cultures from Tg2576 mice overexpressing amyloid-β-precursor protein (APP), transduction with an IGF-2expressing vector caused a significant reduction of the extracellular Aβ42 level measured in the culture medium.…”
Section: Igf-2 Receptorsupporting
confidence: 74%
See 2 more Smart Citations
“…Instead, IGF2 treatment enhanced the nonconventional disposal of soluble polyglutamine peptide species into the extracellular space through the secretion via microvesicles and exosomes. Knockdown of IGF2R decreased almost in half the levels of polyQ79-EGFP secretion, whereas the knockdown of IR or IGF1R did not have any effect on this [49]. Similar results were obtained in a study using a genetic model of AD: in the primary hippocampal cultures from Tg2576 mice overexpressing amyloid-β-precursor protein (APP), transduction with an IGF-2expressing vector caused a significant reduction of the extracellular Aβ42 level measured in the culture medium.…”
Section: Igf-2 Receptorsupporting
confidence: 74%
“…If we arranged all possible receptors by IGF-2 affinity to them, the list would most likely look like this: IGF1R > IGF2R = IR-A = IGF1R / IR-A heterodimer > IR-B = IGF1R / IR-B heterodimer [163]. However, some sources [15,49,156] imply that IGF-2 affinity to IGF2R is higher than to IGF1R.…”
Section: Igf-2 Receptors (Igf1r Ir Igf2r)mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly a recent report directly implicated the activity of IRE1α/RIDD in the downstream modulation of the DNA damage response affecting DNA repair and cell cycle control (Dufey et al, 2020), a pathway that has been extensively connected with the process of senescence. In addition, genetic targeting of XBP1 in the mouse brain was recently shown to trigger protective compesatory events resulting in the upregulation of IGF2, improving proteostasis in models of Huntington's disease (García‐Huerta et al, 2020). Because many small molecules (Hetz et al, 2019) and gene therapy approaches (Valenzuela et al, 2018) are under development to tune the ER proteostasis network in a disease context, interesting opportunities may become available in the near future to target the UPR in the context of aging, which promise an interesting holistic approach to prevent or attenuate the emergence of a variety of age‐related diseases affecting the human population.…”
Section: Perspectivementioning
confidence: 99%
“…In a recently published study, it has been demonstrated that the AAV administration of IGF2 into the striatum of YAC128 and R6/2 mice decreased the levels of mHTT and increased the levels of DARPP-32, a marker used to assess striatal neurons survival (García-Huerta et al, 2020 ). Interestingly, neuroprotective effects of IGF2 treatment have been described in preclinical models of others neurodegenerative diseases such as amyotrophic lateral sclerosis (Allodi et al, 2016 ), spinal muscular atrophy (Brown et al, 2009 ) and Alzheimer’s disease (Pascual-Lucas et al, 2014 ).…”
Section: Neurotrophic Factors-based Therapies For Pd and Hdmentioning
confidence: 99%